Why it pays for aid recipients to take note of the Millennium Challenge Corporation: other donors do! - Dreher, Axel; Nunnenkamp, Peter; Öhler, Hannes (Economics letters, 2012)
We empirically analyze how other aid agencies, within and outside the United States, reacted to the Millennium Challenge Corporation (MCC). We find that positive signaling effects dominate possible substitution effects. Striving for MCC eligibility thus pays.
Gesehen am 17.12.2018
Available online: 29 December 2011